Ethical and legal implications of interventions on ‘unpatients’: therapeutic v. non-therapeutic treatments (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
Advances in modern medicine and technology represent the factual premise to deal with the question of legitimateness and justification of non-strictly therapeutic interventions on a ‘quite new’ class of individuals termed in the 1990s ‘unpatients’. Main aim of this paper is to identify the major ethical and legal aspects concerning this topic today, in order to define the borders of the map traced with regard to the ethical and legal debate some decades ago. A close examination of the ethical dilemmas of non-strictly therapeutic interventions will highlight characteristic perspectives and specificity of treatments administered to unpatients. To some of these peculiarities legal regulation has already provided answers, whereas with regard to other aspects a balance among different principles at stake is needed along with mechanisms set to safeguard their implementation.
Keywords: unpatients; non-therapeutic treatments; medical ethics; enhancement; definition of illness